The Cutting Edge: Surface Texture Analysis following Resection of Nerve Stumps Using Various Instruments. Issue 5 (May 2021) - Rose, Ryan Adam; Bliss, Ryan; Bromage, Timothy; Hu, Bin; Gopman, Jared M.; Melamed, Eitan
Abstract : Background: Preparation of nerve ends is an essential part of nerve repair surgery. Multiple instruments have been described for this purpose; however, no consensus exists regarding which is the least traumatic for tissue handling. We believe that various instruments used for nerve-end excision will lead to different surface roughness. Methods: Median and ulnar nerves from fresh frozen cadavers were dissected, and 1–2 cm lengths were excised using a No. 11 blade, a razor blade, or a pair of scissors. Using electron microscopy, 3-dimensional surface analysis of roughness (Sa) for each specimen was performed using ZeeScan optical hardware and GetPhase software (PhaseView, Buisson, France). An ANOVA or Kruskal-Wallis test compared roughness measures among cutting techniques. Results: Forty nerves were included. Of these, 13 (32.5%) were cut using scissors, 15 (37.5%) using a razor blade, and 12 (30%) using a No. 11 blade. An ANOVA test showed statistical differences in Sa among the cutting techniques ( P = 0.002), with the lowest mean Sa noted in the scissors group (7.2 µM, 95% CI: 5.34–9.06), followed by No. 11 blade (7.29 µM, 95% CI: 5.22–9.35), and razor blade (11.03 µM, 95% CI: 9.43–12.62). Median Ra (surface profile roughness) was 4.58 (IQR: 2.62–5.46). A Kruskal-Wallis test demonstrated statistical difference in Ra among techniques ( P = 0.003), with the lowest by No. 11 blade (3 µM, IQR: 1.87–4.38), followed by scissors (3.29 µM, IQR: 1.56–4.96), and razor (5.41 µM, IQR: 4.95–6.21). Conclusion: This novel technique of 3-dimensional surface analysis found razor blade use demonstrated poor roughness, whereas a No. 11 blade or nerve-specific scissors led to equivocally smooth nerve ends.